2010
DOI: 10.1189/jlb.1009649
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Advance: Interconversion between pure chemotactic ligands and chemoattractant/secretagogue ligands of neutrophil C5a receptor by a single amino acid substitution

Abstract: Skp derived from Escherichia coli attracts leukocytes as a pure chemotactic ligand of the C5a receptor. We identified the submolecular region of Skp that binds and activates the C5a receptor to be -Gln103-Asp104-Arg105- using synthetic peptide fragments and site-directed mutants of Skp. As the C5a amino acid residue equivalent to Gln103 of Skp is Leu72, we prepared a Gln103Leu-Skp mutant as a recombinant protein. With this mutation, Skp gained secretagogue functions including induction of the respiratory burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…However, despite success in animal models, clin- (8,35,52). Although this may be attributable to the perceived promiscuity and redundancy of chemokine receptors and their ligands, it was recently reported that a single amino acid change in a chemoattractant ligand could alter the functional outcome of binding to a single receptor (25). Further studies are necessary to define the functional in vivo specificity of chemokine ligand/receptor interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite success in animal models, clin- (8,35,52). Although this may be attributable to the perceived promiscuity and redundancy of chemokine receptors and their ligands, it was recently reported that a single amino acid change in a chemoattractant ligand could alter the functional outcome of binding to a single receptor (25). Further studies are necessary to define the functional in vivo specificity of chemokine ligand/receptor interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that C5a, mutated at Leu72 to Gln, maintained its chemoattractant capacity but lost its secretagogue capacity in the context of neutrophil stimulation. Additionally, we found that cytoplasmic Ca 2+ influx was absent during the chemotactic response induced in neutrophils exposed to Leu72Gln-C5a [15]. These data suggest that while C5a and Leu72Gln-C5a both ligate the C5a receptor and induce chemotactic migration in neutrophils, the intracellular signaling pathways differ between these ligands.…”
Section: Introductionmentioning
confidence: 74%
“…Although Leu72Gln mutation of C5a allows this protein to maintains its chemoattractant properties, this mutation abolishes its secretagogue and Ca 2+ mobilization capacities in the context of neutrophil stimulation [15]. Here, we examined the properties of this mutant in the context of HMC-1 cell stimulation.…”
Section: Lack Of Inhibitory Effect Of C4a On Hmc-1 Cell Chemotaxis Inmentioning
confidence: 98%
See 1 more Smart Citation
“…We suggested another role of find-me signals in the initiation phase. Their receptors are commonly coupled with Gαiβγ protein (GiPCRs) and/or Gαqβγ protein (GqPCRs), which are classical but not pure chemoattractant receptors [6]. Classical chemoattractant receptors commonly mediate chemotaxis and secretion of at least macrophages and neutrophils, signaling through downstream extracellular signal-regulated kinase 1/2 (ERK1/2), and leading to an enhancement in cytoplasmic calcium mobilization.…”
Section: Introductionmentioning
confidence: 99%